A prospective study of patients with CT detected pallidal calcifications. Issue 6 (June 1993) - Fénelon, G; Gray, F; Paillard, F; Thibierge, M; Mahieux, F; Guillani, A
Abstract : In a prospective study pallidal calcification was detected in 30 of 1478 (2%) adult patients, on CT brain scans. In 8 cases (26%), the calcifications were detected either years after, or during the course of, conditions known to cause basal ganglia calcification, including AIDS in four cases. Eight patients (three with AIDS) had disturbances of calcium and phosphorus metabolism. It was concluded that: a) pallidal calcification is not uncommon and aetiological factors may be recognised more often than previously reported; b) AIDS is emerging as a significant cause of pallidal calcification in young adults, and c) in AIDS and other conditions, abnormal calcium and phosphate metabolism may act in conjunction with local vascular changes.